2021
DOI: 10.3390/en14082046
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transition in Poland—Assessment of the Renewable Energy Sector

Abstract: The topic of the article considers the functioning of the renewable energy (RE) sector in Poland. This is really important in the context of the energy transition of the national economy because it influences the creation of modern technologies and increases the competitiveness and innovation of the country. Poland is in a process of energy transition where the RE sector has been developing for two decades. The authors aimed to research the RE sector improvement possibilities in Poland, including the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 66 publications
2
51
0
Order By: Relevance
“…Despite being lower than the EU average GDP per capita, these countries achieved relatively high results in the analyzed areas, allowing them to qualify for typological groups I or II. These observations are also confirmed by the results of studies by other authors [91][92][93][94][95], which show, among other things, that the relationship between environmental pollution and the wealth of a country has the shape of an inverted letter "U"-with economic growth, the pollution increases, but only to a particular level beyond which environmental pollution decreases with economic growth. In recent years, the above-described curve has flattened, and the peaks at ever-lower levels signify that even poorer countries are beginning to pay more attention to the environment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite being lower than the EU average GDP per capita, these countries achieved relatively high results in the analyzed areas, allowing them to qualify for typological groups I or II. These observations are also confirmed by the results of studies by other authors [91][92][93][94][95], which show, among other things, that the relationship between environmental pollution and the wealth of a country has the shape of an inverted letter "U"-with economic growth, the pollution increases, but only to a particular level beyond which environmental pollution decreases with economic growth. In recent years, the above-described curve has flattened, and the peaks at ever-lower levels signify that even poorer countries are beginning to pay more attention to the environment.…”
Section: Discussionsupporting
confidence: 84%
“…More advanced statistical analysis methods were used to study the relationships between the analyzed areas. The research used a multicriteria taxonomy described in the literature [90][91][92]. The mathematical algorithm of this method takes place in several stages.…”
mentioning
confidence: 99%
“…There are even fewer articles on SWOT/TOWS survey and analysis. Pietrzak et al (2021) described the current state and prospects for the development of RE in Poland based on sociometric surveys conducted among RE experts in groups on social networks. It was found that the sun, wind and biomass energy have the greatest chances for development.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Small support for micro and small energy sources of private individuals is a threat. While public utility institutions can expect the co-financing, in case of individual clients, support is small (Pietrzak et al, 2021).…”
Section: Threatsmentioning
confidence: 99%
“…However, the distribution of power plants across the country is not regular (Poland is divided into 16 provinces). The highest power is generated in Zachodniopomorskie province (1800 MW) and the lowest in Małopolskie province (150 MW) [14]. The availability of different types of renewable energy sources depends on geographical location (e.g., the highest wind power is recorded in the northern regions of Poland) and agricultural use of soils (the most suitable for the construction of wind turbines is low-class land and located at a significant distance from wooded areas).…”
Section: Introductionmentioning
confidence: 99%